The Effect of Idealized Influence, Inspirational Motivation, Intellectual Stimulation, and Individual Consideration on HR Performance - Sutanto, Hery; Utami, Yekti; Diantoro, Aris Kusumo (RSF Conference Series: Business, Management and Social Sciences, 2021)
Idealized Influence, Inspirational Motivation, and intellectual stimulation are transformational leadership's main components. Subordinates are encouraged to elevate their awareness and become committed to their mission and vision due to Inspirational motivation. Idealized Influence is related to the behavior of leaders with a transformational style that is able to generate trust, admiration, comity, and eagerness from subordinates to imitate the leader. Intellectual stimulation is a dimension of transformational leadership styles that encourages human resources to be innovative. The purpose of this study is to empirically know the Influence of idealized Influence, inspirational motivation, and intellectual stimulation on HR performance. This research uses a quantitative research design. The sample in this study was the santri Ponpes Anwar Futuhiyyah. Purposive sampling techniques are used to obtain samples. Multiple regression techniques are used to analyze data by using the software of SPSS.